Comparative Analysis of English Language Learners' Errors across Different Linguistic Backgrounds - Ogunyemi, Kehinde Olufemi (American International Journal of Social Science Research, 2019)
The focus of the study is the comparative analysis of English as a second language learners’ errors across different linguistic backgrounds in Nigeria. The study adopted the descriptive research design. The population for the study consisted of senior secondary school students in Ondo State. A simple random sampling technique was employed to select four secondary schools and 26 students from four schools in Akoko Ondo State(12 male, 14 female). The sample consisted students from three linguistic backgrounds (Igbo, Yoruba, and Hausa). The instrument used to gather data was a verbal ability test. The reliability of the instrument was determined through the test- retest method (r = 0.83). Four research questions were answered. The findings revealed that there was a significant difference in the scores of students from different linguistic backgrounds in their use of tenses, pronouns, spellings and pronunciation. On the basis of these findings it was recommended that students are to be given time to pay attention to their use of English tenses, pronoun, spelling and pronunciation so as to maximize their academic potentials and possibilities. There is need to give teachers chance to experience in-service training and seminars. This will make them conversant with current development in pedagogy and language itself.